IDNLearn.com: Your go-to resource for finding expert answers. Our community provides accurate and timely answers to help you understand and solve any issue.
Sagot :
Answer:
4n^2.
Step-by-step explanation:
Working from left to right in the square parentheses:-
[6m² x 6n² ÷ 9mn ÷ 2m]²
= [(36m^2n^2 / 9mn) / 2m]^2
= (4mn / 2m)^2
= (2n)^2
= 4n^2.
given:
[6m² x 6n² ÷ 9mn ÷ 2m]²
to find:
the simplest form.
solution:
[tex] (\frac{6 {m}^{2} \times (6 {n}^{2} ) \div 9mn {}^{} }{2m} ) {}^{2} [/tex]
[tex] = \binom{ \frac{2 {m}^{2} \times (6 {n}^{2}) }{3mn} }{2m} {}^{2} [/tex]
[tex] = \binom{ \frac{2m \times (2 {n}^{2}) }{n} }{2m} {}^{2} [/tex]
[tex] = ( \frac{m \times (2n)}{m} ) {}^{2} [/tex]
[tex] = (2n {)}^{2} [/tex]
[tex] = 4 {n}^{2} [/tex]
Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.